2016
DOI: 10.1212/wnl.0000000000002331
|View full text |Cite
|
Sign up to set email alerts
|

How temporal evolution of intracranial collaterals in acute stroke affects clinical outcomes

Abstract: Objective: We compared intracranial collaterals on pretreatment and day 2 brain CT angiograms (CTA) to assess their evolution and relationship with functional outcomes in acute ischemic stroke (AIS) patients treated with IV tissue plasminogen activator (tPA).Methods: Consecutive AIS patients who underwent pretreatment and day 2 CTA and received IV tPA during 2010-2013 were included. Collaterals were evaluated by 2 independent neuroradiologists using 3 predefined criteria: the Miteff system, the Maas system, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 30 publications
0
30
0
Order By: Relevance
“…This is in agreement with previous studies showing that a better collateral score was associated with smaller infarcts and slower IGR. [14][15][16][17][18][19][20] In patients with no collaterals, the IGR could reach 31.56 ml/log(min).…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with previous studies showing that a better collateral score was associated with smaller infarcts and slower IGR. [14][15][16][17][18][19][20] In patients with no collaterals, the IGR could reach 31.56 ml/log(min).…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, collateral flow is dynamic and changes over time. Yeo et al (35) found that an improvement in collateral grade over time assessed using CTA in patients without recanalization was associated with worse outcome and mortality. Such slower recruitment of collaterals is mediated by metabolic factors and angiogenesis, as compared to the rapid response due to drop in perfusion pressure and relaxation of smooth muscles with a resulting pressure gradient (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, causality was uncertain given the delayed follow-up assessment (day 3-5), when extensive infarction and edema can severely impede retrograde (or anterograde) flow. Interestingly, using CT-angiography, Yeo et al 17 recently reported that in patients without recanalization or with poor collaterals at baseline, late (i.e. 24 h) recruitment of cortical collaterals was associated with worse clinical outcome and higher mortality.…”
Section: Discussionmentioning
confidence: 99%
“…14 In our previous work, lower hypoperfusion intensity ratio (proportion of voxels with T max !7 s within the T max !2 s lesion), an indirect marker of good collaterals, was observed at baseline in patients showing subsequent reperfusion without recanalization. 3 Still, only limited data so far have related the evolution of collateral flow to infarct growth 13 or clinical outcome, 17 and these studies explored late follow-up time points only (i.e. !24 h).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation